A survey of nutritional education within the Holiday Activities and Food programme across England - Emily K. Round; Paul B. Stretesky; Margaret Anne Defeyter (Frontiers Media S.A., 2024)
BackgroundNutritional education is a mandatory component of the Holiday Activities and Food (HAF) programme in England, yet there is a paucity of literature exploring how this component is delivered. The aim of this study was therefore to explore the delivery, content, dose and perceived impacts of nutritional education, at the HAF club level, across England.MethodsA self-completion, cross-sectional online survey design was adopted. Non-probability purposive sampling was used to collect data from HAF club leads (n = 147) from across England. Data were analysed using descriptive statistics and frequencies.FindingsFace-to-face nutritional education was the most common mode of delivery, with sessions mostly comprising of discussing food and nutrition. However, whilst the majority of clubs delivered the required number of nutritional education sessions per week, according to the Department for Education's guidelines, the time spent delivering individual nutritional education activities may not be sufficient to drive change in related skills and behaviours. Moreover, many clubs did not adopt a whole-family approach, and some did not deliver any nutritional education activities at all, which club leads attributed to a lack of material resources and ambiguity in the national HAF guidance.ConclusionNutritional education is delivered in a variety of ways across HAF clubs, based upon available local assets, resources and venues. Policy and practice recommendations include increased HAF funding to support clubs that lack material resources, national training in nutritional education, and evidence-informed guidance and practice.